Global Fecal and Plasma Metabolic Dynamics Related to Helicobacter pylori Eradication - Yap, Theresa Wan-Chen; Leow, Alex Hwong-Ruey; Azmi, Ahmad Najib; Callahan, Damien L.; Perez-Perez, Guillermo I.; Loke, Mun-Fai; Goh, Khean-Lee; Vadivelu, Jamuna (Frontiers in Microbiology, 2017)
Background: Helicobacter pylori colonizes the gastric mucosa of more than half of the world’s population. There is increasing evidence H. pylori protects against the development of obesity and childhood asthma/allergies in which the development of these diseases coincide with transient dysbiosis. However, the mechanism underlying the association of H. pylori eradication with human metabolic and immunological disorders is not well-established. In this study, we aimed to investigate the local and systemic effects of H. pylori eradication through untargeted fecal lipidomics and plasma metabolomics approaches by liquid chromatography mass spectrometry (LC-MS). Results: Our study revealed that eradication of H. pylori eradication (i.e. loss of H. pylori and/or H. pylori eradication therapy) dramatically changed many global metabolite/lipid features, with the majority being down-regulated. Our findings primarily show that H. pylori eradication affects the host energy and lipid metabolism which may eventually lead to the development of metabolic disorders. Conclusion: These predictive metabolic signatures of metabolic and immunological disorders following H. pylori eradication can provide insights into dynamic local and systemic metabolism related to H. pylori eradication in modulating human health.